The university environment and its impact on the cultural values of college students - otmen, saadia; ali charif, houria (Journal of Social Sciences and Humanities, 2024)
The university is one of the most fundamental pillars upon which society relies to preserve its identity, cultural heritage, and achievements. Its role goes beyond the mere transmission of knowledge and various sciences to students and their academic formation; it is also a place to enhance and solidify various values, particularly cultural values that express the society's identity, a fundamental condition for its stability, and the realization of its societal security. In the context of the scientific, technological, and cultural changes of our time, accompanied by negatives, threats, and intrusions into the privacy of society and its individuals, particularly the youth, universities are currently required to provide an attractive and dynamically conducive environment. This enables them to better confront and address these challenges, as well as to reinforce and promote various values in students, primarily cultural and religious values. This should be based on development, investment, and the utilization of all available resources, both material and human. It also involves efficient management and the harnessing of its scholarly competencies, all in the service of both the individual and society. This is what we aim to discuss and demonstrate through this research paper, guided by a primary question: What is the impact of the university environment on the solidification of cultural values in university students?